Decline of deep and bottom water ventilation and slowing down of anthropogenic carbon storage in the Weddell Sea, 1984-2011 - Huhn, Oliver; Rhein, Monika; Hoppema, Mario; van Heuven, Steven (Deep Sea Research Part I: Oceanographic Research Papers, 2013)
We use a 27 year long time series of repeated transient tracer observations to investigate the evolution of the ventilation time scales and the related content of anthropogenic carbon (C-ant) in deep and bottom water in the Weddell Sea. This time series consists of chlorofluorocarbon (CFC) observations from 1984 to 2008 together with first combined CFC and sulphur hexafluoride (SF6) measurements from 2010/2011 along the Prime Meridian in the Antarctic Ocean and across the Weddell Sea. Applying the Transit Time Distribution (TTD) method we find that all deep water masses in the Weddell Sea have been continually growing older and getting less ventilated during the last 27 years. The decline of the ventilation rate of Weddell Sea Bottom Water (WSBW) and Weddell Sea Deep Water (WSDW) along the Prime Meridian is in the order of 15-21%; the Warm Deep Water (WDW) ventilation rate declined much faster by 33%. About 88-94% of the age increase in WSBW near its source regions (1.8-2.4 years per year) is explained by the age increase of WDW (4.5 years per year). As a consequence of the aging, the C-ant increase in the deep and bottom water formed in the Weddell Sea slowed down by 14-21% over the period of observations. (C) 2013 Published by Elsevier Ltd.